Hollow resin particles, their production method, and uses

Hollow resin particles with an etheric shell structure, produced using a specific reaction method, address the challenges of achieving low dielectric properties and high heat resistance, while reducing water absorption and simplifying manufacturing.

JP7656123B2Active Publication Date: 2025-04-02SEKISUI PLASTICS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024077052
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-17
Filing Date
2024-05-10
Publication Date
2025-04-02
Estimated Expiration
2041-12-09

AI Technical Summary

Technical Problem

Existing hollow resin particles fail to achieve a balance of low dielectric constant, low dielectric loss tangent, and high heat resistance, while also having issues with water absorption and complex manufacturing processes.

Method used

Development of hollow resin particles with a shell portion having an etheric structure, which are produced using a method involving a compound with an ether structure and a monomer, reacted in an aqueous medium with a non-reactive solvent, to achieve the desired properties.

Benefits of technology

The resulting hollow resin particles exhibit excellent heat resistance, low dielectric constant, and low dielectric loss tangent, while minimizing water absorption, and simplify the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656123000014
    Figure 0007656123000014
  • Figure 0007656123000015
    Figure 0007656123000015
  • Figure 0007656123000016
    Figure 0007656123000016
Patent Text Reader

Abstract

To provide: a hollow resin particle that has a shell portion and a hollow portion surrounded by the shell portion and that can achieve reductions in dielectricity and dielectric loss tangent and can exhibit excellent heat resistance; a method of producing such a hollow resin particle in a simple manner; and a use of such a hollow resin particle.SOLUTION: A hollow resin particle according to an embodiment of the present invention includes a shell portion and a hollow portion surrounded by the shell portion, wherein the shell portion has an ether structure represented by formula (1).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to hollow resin particles, a method for producing the same, and uses thereof. [Background technology]

[0002] In order to increase the speed of information processing using electronic devices, attempts have been made to reduce the dielectric constant and dielectric loss tangent of the insulating layer of a multilayer printed circuit board. As part of these attempts, studies have been made to introduce air space into the resin layer by mixing hollow particles, each of which has a shell portion and a hollow portion surrounded by the shell portion, into a thermosetting resin, thereby reducing the dielectric constant and dielectric loss tangent.

[0003] Hollow resin particles used for such applications are required to have high heat resistance so that the hollow resin particles do not undergo substantial change even when heated, for example, during molding of the thermosetting resin in which the hollow resin particles are mixed or during use of solder.

[0004] Furthermore, if moisture is present in the hollow resin particles, the moisture may evaporate and become outgassed during heating as described above, which may impair the reliability of the insulating layer. For this reason, hollow resin particles used for such purposes are required to have a low water absorption rate.

[0005] It has been reported that hollow acrylic resin particles can be obtained by suspension polymerization of a monomer mainly composed of an acrylic polyfunctional monomer such as trimethylolpropane tri(meth)acrylate or dipentaerythritol hexaacrylate together with a hydrophobic solvent (Patent Document 1).

[0006] It has been reported that hollow resin particles having a hollow space surrounded by a shell and consisting of multiple hollow regions can be obtained by suspension polymerization of a monomer mainly composed of an acrylic polyfunctional monomer such as trimethylolpropane tri(meth)acrylate and an acrylic monofunctional monomer such as methyl methacrylate together with a hydrophobic solvent (Patent Document 2).

[0007] It has been reported that styrene-based hollow resin particles can be obtained by suspension polymerization of divinylbenzene together with saturated hydrocarbons having 8 to 18 carbon atoms (more specifically, hexadecane) (Patent Document 3).

[0008] It has been reported that hollow resin particles obtained by polymerizing a polyfunctional monomer and a monofunctional monomer can be blended with a resin to produce an organic insulating material with excellent insulating properties, a low dielectric constant, and a low dielectric tangent. Specific monomers that have been used include styrene, methyl methacrylate, divinylbenzene, and trimethylolpropane tri(meth)acrylate (Patent Document 4).

[0009] As hollow resin particles, a shell made of either a polymer or copolymer of a crosslinkable monomer, or a copolymer of the crosslinkable monomer and a monofunctional monomer and having a single-phase structure, typically a styrene-based hollow resin particle obtained by suspension polymerization of divinylbenzene together with a saturated hydrocarbon having 8 to 18 carbon atoms (more specifically, hexadecane), has been reported, and it has been reported that a resin composition containing the hollow resin particles and a thermosetting resin is suitable for producing multilayer printed circuit boards used in electronic devices, etc. (Patent Document 5).

[0010] In general, it is known that acrylic resins have high values ​​of dielectric constant and dielectric loss tangent, insufficient heat resistance, and high water absorption. For these reasons, the acrylic hollow resin particles described in Patent Documents 1 and 2 are not suitable for the purpose of lowering the dielectric constant and dielectric loss tangent of a resin layer, imparting high heat resistance to a resin layer, and suppressing the water absorption of a resin layer.

[0011] The styrene-based hollow resin particles described in Patent Document 3 are made of a material (crosslinked polystyrene) that has a low relative dielectric constant and dielectric loss tangent compared to acrylic hollow resin particles. Therefore, it can be said that the particles are effective for the purpose of reducing the dielectric constant and dielectric loss tangent of the resin layer. However, since saturated hydrocarbons having 8 to 18 carbon atoms (specifically, hexadecane) are used in the production thereof, it is difficult to remove the solvent from the hollow portion by distillation or the like, and saturated hydrocarbons having 8 to 18 carbon atoms remain in the obtained styrene-based hollow resin particles, making it difficult to obtain styrene-based hollow resin particles in which the hollow portion is completely replaced with air. In addition, in order to obtain styrene-based hollow resin particles in which the hollow portion is completely replaced with air, production costs are incurred for the solvent removal as described above. Furthermore, the styrene-based hollow resin particles described in Patent Document 3 have insufficient heat resistance.

[0012] The hollow resin particles described in Patent Document 4 use a styrene monomer in combination with an acrylic monomer having a high dielectric constant and dielectric dissipation factor, and therefore the resin layer is insufficiently low in dielectric constant and dielectric dissipation factor.In addition, Patent Document 4 indicates, as a guideline for heat resistance, the 10% weight loss temperature measured by TG-DTA in a nitrogen atmosphere at a temperature rise rate of 10°C / min, but the heat resistance is insufficient.

[0013] The hollow resin particles described in Patent Document 5, like the styrene-based hollow resin particles described in Patent Document 3, are produced using saturated hydrocarbons having 8 to 18 carbon atoms (more specifically, hexadecane), making it difficult to remove the solvent from the hollow parts by distillation or the like, and saturated hydrocarbons having 8 to 18 carbon atoms remain in the obtained styrene-based hollow resin particles, making it difficult to obtain styrene-based hollow resin particles in which the hollow parts are completely replaced with air. In addition, in order to obtain styrene-based hollow resin particles in which the hollow parts are completely replaced with air, production costs are incurred for the above-mentioned solvent removal. Furthermore, the styrene-based hollow resin particles described in Patent Document 5 have insufficient heat resistance. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] Patent No. 6513273 [Patent Document 2] Patent No. 4445495 [Patent Document 3] JP 2002-080503 A [Patent Document 4] JP 2000-313818 A [Patent Document 5] Patent No. 4171489 Summary of the Invention [Problem to be solved by the invention]

[0015] The present invention has been made to solve the above-mentioned problems of the prior art, and its main object is to provide hollow resin particles having a shell portion and a hollow portion surrounded by the shell portion, which can achieve low dielectric constant and low dielectric loss tangent and can exhibit excellent heat resistance. It is also an object of the present invention to provide a method for easily producing such hollow resin particles. It is also an object of the present invention to provide uses of such hollow resin particles. [Means for solving the problem]

[0016] The hollow resin particles according to an embodiment of the present invention are A hollow resin particle having a shell portion and a hollow portion surrounded by the shell portion, The shell portion has an ether structure represented by formula (1). [ka]

[0017] In one embodiment, the hollow resin particles according to the embodiment of the present invention have an average particle size of 0.1 μm to 50.0 μm.

[0018] In one embodiment, the hollow portion consists of one hollow region.

[0019] In one embodiment, the hollow portion comprises a plurality of hollow regions.

[0020] In one embodiment, the hollow portion has a porous structure.

[0021] In one embodiment, the hollow resin particles have a 5% thermal weight loss temperature of 300° C. or higher when heated at a rate of 10° C. / min in a nitrogen atmosphere.

[0022] In one embodiment, the hollow resin particles according to the embodiment of the present invention are used in a resin composition for a semiconductor member.

[0023] In one embodiment, hollow resin particles according to embodiments of the present invention are used in a coating composition.

[0024] In one embodiment, the hollow resin particles according to the embodiment of the present invention are used in a heat insulating resin composition.

[0025] In one embodiment, the hollow resin particles according to the embodiment of the present invention are used in a light-diffusing resin composition.

[0026] In one embodiment, the hollow resin particles according to the embodiment of the present invention are used in a light diffusing film.

[0027] The resin composition for a semiconductor member according to an embodiment of the present invention contains the hollow resin particles according to an embodiment of the present invention.

[0028] A coating composition according to an embodiment of the present invention includes hollow resin particles according to an embodiment of the present invention.

[0029] The heat insulating resin composition according to an embodiment of the present invention includes hollow resin particles according to an embodiment of the present invention.

[0030] The light-diffusing resin composition according to an embodiment of the present invention contains hollow resin particles according to an embodiment of the present invention.

[0031] The light diffusing film according to an embodiment of the present invention includes hollow resin particles according to an embodiment of the present invention.

[0032] A manufacturing method according to an embodiment of the present invention includes: A method for producing hollow resin particles according to an embodiment of the present invention, comprising the steps of: 20 to 80 parts by weight of a compound (A) having an ether structure represented by formula (1) and 80 to 20 parts by weight of a monomer (B) that reacts with the compound (A) (the total amount of the compound (A) and the monomer (B) being 100 parts by weight) are reacted in an aqueous medium in the presence of a non-reactive solvent. [ka] Effect of the Invention

[0033] According to an embodiment of the present invention, it is possible to provide hollow resin particles having a shell portion and a hollow portion surrounded by the shell portion, which can achieve low dielectric constant and low dielectric loss tangent and exhibit excellent heat resistance. It is also possible to provide a method for easily producing such hollow resin particles. Furthermore, it is also possible to provide uses of such hollow resin particles. [Brief description of the drawings]

[0034] [Figure 1] FIG. 4 is a schematic cross-sectional view illustrating the structure of a hollow portion. [Diagram 2] FIG. 2 is a cross-sectional photograph of the hollow resin particle (1) obtained in Example 1. [Diagram 3] FIG. 2 is a cross-sectional photograph of the hollow resin particle (2) obtained in Example 2. [Figure 4] FIG. 2 is a cross-sectional photograph of the hollow resin particle (3) obtained in Example 3. [Diagram 5] FIG. 2 is a cross-sectional photograph of the hollow resin particle (4) obtained in Example 4. [Figure 6] FIG. 1 is a cross-sectional photograph of a hollow resin particle (5) obtained in Example 5. [Figure 7]FIG. 2 is a cross-sectional photograph of the hollow resin particle (6) obtained in Example 6. [Figure 8] FIG. 1 is a cross-sectional photograph of a hollow resin particle (7) obtained in Example 7. [Figure 9] FIG. 1 is a TEM photograph of hollow resin particles (8) obtained in Example 8. [Figure 10] FIG. 1 is a TEM photograph of hollow resin particles (9) obtained in Example 9. [Figure 11] FIG. 2 is a cross-sectional photograph of the hollow resin particle (10) obtained in Example 10. [Figure 12] FIG. 1 is a cross-sectional photograph of a hollow resin particle (11) obtained in Example 11. [Figure 13] FIG. 2 is a cross-sectional photograph of the particle (C1) obtained in Comparative Example 1. [Figure 14] FIG. 2 is a TEM photograph of particles (C2) obtained in Comparative Example 2. [Figure 15] FIG. 2 is an ultraviolet-visible-near infrared spectroscopic reflectance spectrum of the hollow resin particles (1) obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0036] ≪≪1. Hollow resin particles≫≫ ≪1-1. Structure and characteristics of hollow resin particles≫ The hollow resin particles according to the embodiment of the present invention are hollow resin particles having a shell portion and a hollow portion surrounded by the shell portion. Here, "hollow" means that the inside is filled with a substance other than resin, such as a gas or liquid, and preferably means that the inside is filled with a gas in order to more effectively exhibit the effects of the present invention.

[0037] The shell portion and the hollow portion surrounded by the shell portion may consist of one hollow region, as shown in the schematic cross-sectional view of FIG. 1(a), or may consist of multiple hollow regions, as shown in the schematic cross-sectional view of FIG. 1(b).

[0038] The shell part and the hollow part surrounded by the shell part may have a porous structure as shown in the schematic cross-sectional view of Fig. 1(c) In this way, when the hollow part has a porous structure, the hollow part may be composed of one hollow region (continuous pores), multiple hollow regions (independent pores), or a mixture of these.

[0039] The average particle diameter of the hollow resin particles according to the embodiment of the present invention is preferably 0.1 μm to 50.0 μm, more preferably 0.1 μm to 40.0 μm, even more preferably 0.2 μm to 30.0 μm, and particularly preferably 0.3 μm to 20.0 μm. If the average particle diameter of the hollow resin particles is within the above range, the effects of the present invention can be more effectively achieved. If the average particle diameter of the hollow resin particles according to the embodiment of the present invention is too small outside the above range, the thickness of the shell portion becomes relatively thin, and the hollow resin particles may not have sufficient strength. If the average particle diameter of the hollow resin particles according to the embodiment of the present invention is too large outside the above range, phase separation between the polymer and the solvent produced by polymerization of the monomer component during suspension polymerization may be difficult to occur, which may make it difficult to form the shell portion.

[0040] The hollow resin particles according to the embodiment of the present invention preferably have a 5% thermal weight loss temperature of 300°C or more, more preferably 320°C or more, even more preferably 340°C or more, and particularly preferably 360°C or more, when heated in a nitrogen atmosphere at 10°C / min. The upper limit of the 5% thermal weight loss temperature is preferably 500°C or less in reality. If the 5% thermal weight loss temperature of the hollow resin particles according to the embodiment of the present invention when heated in a nitrogen atmosphere at 10°C / min is within the above range, the hollow resin particles according to the embodiment of the present invention can exhibit excellent heat resistance. If the 5% thermal weight loss temperature of the hollow resin particles according to the embodiment of the present invention when heated in a nitrogen atmosphere at 10°C / min is too small outside the above range, for example, when the hollow resin particles are mixed with a thermosetting resin, the particles are deformed by heating for the curing reaction, and the hollow portion is lost, which may reduce the low dielectric effect and the low dielectric tangent effect.

[0041] The hollow resin particles according to the embodiment of the present invention preferably have a moisture content of 0.50% by weight or less, more preferably 0.45% by weight or less, even more preferably 0.40% by weight or less, and particularly preferably 0.35% by weight or less after being left to stand for 96 hours under an atmosphere of 40°C and 95% RH. The lower the moisture content, the better, and preferably 0% by weight or more. If the moisture content of the hollow resin particles after being left to stand for 96 hours under an atmosphere of 40°C and 95% RH is within the above range, the effect of the present invention can be more effectively exhibited. If the moisture content of the hollow resin particles after being left to stand for 96 hours under an atmosphere of 40°C and 95% RH is too high outside the above range, the water absorption rate of the hollow resin particles may be high.

[0042] ≪1-2.Shell part≫ The shell portion has an ether structure represented by formula (1). [ka]

[0043] The shell portion preferably contains a polymer (P) having an ether structure represented by formula (1). When the shell portion contains such a polymer (P), the effects of the present invention can be more effectively exhibited.

[0044] The polymer (P) may be of only one type, or of two or more types.

[0045] The content of the polymer (P) in the shell portion is preferably 60% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 80% by weight to 100% by weight, and particularly preferably 90% by weight to 100% by weight, in order to further exert the effects of the present invention.

[0046] The shell portion may contain any appropriate other components as long as the effects of the present invention are not impaired.

[0047] <Polymer (P)> As the polymer (P), any suitable polymer may be used as long as it has the ether structure represented by formula (1) and does not impair the effects of the present invention. In terms of being able to more effectively exhibit the effects of the present invention, such a polymer (P) is preferably a polymer obtained by reacting a compound (A) having an ether structure represented by formula (1) with a monomer (B) that reacts with the compound (A).

[0048] The compound (A) having an ether structure represented by formula (1) may be of one type only, or of two or more types.

[0049] The monomer (B) to be reacted with the compound having an ether structure represented by formula (1) may be of only one type, or of two or more types.

[0050] The ratio of compound (A) to monomer (B) is preferably (20 parts by weight to 80 parts by weight):(80 parts by weight to 20 parts by weight) in terms of parts by weight (compound (A):monomer (B)), assuming the total amount of compound (A) and monomer (B) to be 100 parts by weight.

[0051] As one embodiment of the above-mentioned preferable ratio, it is more preferably (50 parts by weight to 80 parts by weight):(50 parts by weight to 20 parts by weight), further preferably (55 parts by weight to 75 parts by weight):(45 parts by weight to 25 parts by weight), and particularly preferably (60 parts by weight to 70 parts by weight):(40 parts by weight to 30 parts by weight).

[0052] As another embodiment of the above-mentioned preferable ratio, it is more preferably (30 parts by weight to 70 parts by weight):(70 parts by weight to 30 parts by weight), even more preferably (35 parts by weight to 65 parts by weight):(65 parts by weight to 35 parts by weight), and particularly preferably (40 parts by weight to 60 parts by weight):(60 parts by weight to 40 parts by weight).

[0053] If the content of compound (A) is too small outside the above range, the heat resistance may be insufficient, whereas if the content of compound (A) is too large outside the above range, it may be difficult to form a shell portion and a hollow portion surrounded by the shell portion.

[0054] As the compound (A), any appropriate compound may be adopted as long as it has the ether structure represented by formula (1) and does not impair the effects of the present invention. In terms of being able to more effectively exhibit the effects of the present invention, such a compound (A) is preferably polyphenylene ether. Examples of commercially available polyphenylene ether products include those under the trade name "Noryl" (manufactured by SABIC Corporation), the trade name "Iupiace" (manufactured by Mitsubishi Chemical Corporation), the trade name "Zylon" (manufactured by Asahi Kasei Corporation), and the trade name "OPE-2St" (manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0055] From the viewpoint of compatibility with the non-reactive solvent described below and the ability to more easily prepare hollow resin particles with excellent heat resistance, the polyphenylene ether is preferably an oligomer and preferably has a number average molecular weight (Mn) of 500 to 3,500.

[0056] Examples of the monomer (B) include crosslinkable monomers and monofunctional monomers. In terms of being able to more effectively exhibit the effects of the present invention, a monomer that reacts with the terminal group of the compound (A) is preferred.

[0057] Examples of the crosslinkable monomer include polyfunctional (meth)acrylic acid esters such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and glycerin tri(meth)acrylate; polyfunctional acrylamide derivatives such as N,N'-methylenebis(meth)acrylamide and N,N'-ethylenebis(meth)acrylamide; polyfunctional allyl derivatives such as diallylamine and tetraallyloxyethane; and aromatic crosslinkable monomers such as divinylbenzene, divinylnaphthalene, and diallylphthalate. In terms of being able to more effectively exhibit the effects of the present invention, the crosslinkable monomer is preferably an aromatic crosslinkable monomer, and more preferably divinylbenzene. The crosslinkable monomer may be one type only, or two or more types.

[0058] Examples of the monofunctional monomer include alkyl (meth)acrylic acid esters having 1 to 16 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and cetyl (meth)acrylate; aromatic monofunctional monomers, such as styrene, α-methylstyrene, ethylvinylbenzene, vinyltoluene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, vinylbiphenyl, and vinylnaphthalene; dicarboxylic acid ester monomers, such as dimethyl maleate, diethyl fumarate, dimethyl fumarate, and diethyl fumarate; maleic anhydride; N-vinylcarbazole; and (meth)acrylonitrile. In terms of being able to more effectively exhibit the effects of the present invention, the monofunctional monomer is preferably an aromatic monofunctional monomer, and more preferably styrene or ethylvinylbenzene. The monofunctional monomer may be one type only, or two or more types.

[0059] The polymer (P) can typically be formed by the reaction of a compound (A) with a monomer (B).

[0060] The reaction of the compound (A) with the monomer (B) can be carried out by any appropriate reaction as long as it does not impair the effects of the present invention. As such a reaction, a suspension polymerization reaction is preferable.

[0061] When carrying out a suspension polymerization reaction, typically, an oil phase is added to an aqueous phase and suspended to carry out a polymerization reaction. The aqueous phase or the oil phase may contain any appropriate solvent within a range that does not impair the effects of the present invention. Examples of such solvents include aqueous media and non-reactive solvents as described below. The solvent may be one type only or two or more types.

[0062] When reacting the compound (A) with the monomer (B), any suitable additive (C) that does not correspond to either the compound (A) or the monomer (B) may be used within a range that does not impair the effects of the present invention. The additive (C) may be one type or two or more types. The additive here does not include solvents such as aqueous media and non-reactive solvents as described below.

[0063] The content of the additive (C) is preferably 0 to 40% by weight, more preferably 0 to 30% by weight, even more preferably 0 to 20% by weight, and particularly preferably 0 to 10% by weight, based on the total amount of the compound (A) and the monomer (B).

[0064] Any suitable additive may be used as the additive (C) as long as it does not impair the effects of the present invention. Examples of such additive (C) include a non-crosslinkable polymer, a dispersion stabilizer, a surfactant, and a polymerization initiator.

[0065] By including a non-crosslinkable polymer as the additive (C), phase separation between the polymer (P) produced as the reaction proceeds and the solvent is promoted, and shell formation can be promoted.

[0066] The non-crosslinkable polymer may be, for example, at least one selected from the group consisting of polyolefins, styrene-based polymers, (meth)acrylic acid-based polymers, and styrene-(meth)acrylic acid-based polymers.

[0067] Examples of polyolefins include polyethylene, polypropylene, polyα-olefins, etc. From the viewpoint of solubility in the monomer composition, it is preferable to use a side-chain crystalline polyolefin using a long-chain α-olefin as a raw material, a low-molecular-weight polyolefin produced with a metallocene catalyst, or an olefin oligomer.

[0068] Examples of styrene-based polymers include polystyrene, styrene-acrylonitrile copolymers, and acrylonitrile-butadiene-styrene copolymers.

[0069] Examples of the (meth)acrylic acid-based polymer include polymethyl(meth)acrylate, polyethyl(meth)acrylate, polybutyl(meth)acrylate, and polypropyl(meth)acrylate.

[0070] Examples of styrene-(meth)acrylic acid polymers include styrene-methyl (meth)acrylate copolymers, styrene-ethyl (meth)acrylate copolymers, styrene-butyl (meth)acrylate copolymers, and styrene-propyl (meth)acrylate copolymers.

[0071] ≪1-3. Dielectric constant of hollow resin particles≫ The dielectric constant of the hollow resin particles according to the embodiment of the present invention is preferably 1.0 to 2.5, more preferably 1.0 to 2.4, and even more preferably 1.0 to 2.3. When the dielectric constant of the hollow resin particles according to the embodiment of the present invention is within the above range, the effects of the present invention can be more effectively exhibited. When the dielectric constant of the hollow resin particles according to the embodiment of the present invention exceeds 2.5, even if the hollow resin particles are mixed with, for example, a thermosetting resin, a sufficient dielectric reduction effect cannot be obtained.

[0072] The dielectric constant of the hollow resin particles according to the embodiment of the present invention can be calculated, for example, by referring to "Dielectric Constant of a Mixture" (Applied Physics, Vol. 27, No. 8 (1958)). If the dielectric constant of the mixture of the dispersion medium and hollow resin particles is ε, the dielectric constant of the base material (e.g., a resin composition such as polyimide or epoxy) serving as the dispersion medium is ε1, the dielectric constant of the hollow resin particles is ε2, and the volume fraction of the hollow resin particles in the mixture is φ, the following formula is established. In other words, if ε, ε1, and φ are experimentally determined, the dielectric constant ε2 of the hollow resin particles can be calculated.

number

[0073] The volume fraction φ of the hollow resin particles in the mixture of the dispersion medium and the hollow resin particles can be determined as follows.

number

[0074] The density of the hollow resin particles was measured using a pycnometer (TQC 50 mL specific gravity bottle, manufactured by Cortec Co., Ltd.) and a liquid polymer product called "ARUFON (trademark) UP-1080" (manufactured by Toa Gosei Co., Ltd., density 1.05 g / cm 3 ) can be experimentally determined. Specifically, hollow resin particles and ARUFON UP-1080 are defoamed and mixed using a planetary mixer defoamer (KURABO Corporation, "Mazerustar KK-250") so that the ratio of hollow resin particles is 10% by weight, to prepare a mixture for evaluation. The mixture for evaluation is filled into a 50 mL pycnometer, and the weight of the filled mixture for evaluation is calculated by subtracting the weight of the empty pycnometer from the weight of the pycnometer filled with the mixture. The density of the hollow resin particles can be calculated from this value using the following formula.

number

[0075] <1-4. Uses of hollow resin particles> The hollow resin particles according to the embodiment of the present invention can be used in various applications. In that the effects of the present invention can be more effectively utilized, the hollow resin particles according to the embodiment of the present invention are suitable for semiconductor members, and can be typically used in resin compositions for semiconductor members. In addition, the hollow resin particles according to the embodiment of the present invention can be used in applications such as paint compositions, cosmetics, paper coating compositions, heat insulating compositions, light diffusing compositions, and light diffusing films, in addition to the above-mentioned applications for resin compositions for semiconductor members.

[0076] <Resin composition for semiconductor members> The hollow resin particles according to the embodiment of the present invention can achieve low dielectric constant and low dielectric loss tangent and exhibit excellent heat resistance, and therefore can be suitably used in resin compositions for semiconductor members.

[0077] The resin composition for a semiconductor member according to an embodiment of the present invention contains the hollow resin particles according to an embodiment of the present invention.

[0078] The term "semiconductor member" refers to a member that constitutes a semiconductor, and examples of such members include a semiconductor package and a semiconductor module. In this specification, the term "resin composition for a semiconductor member" refers to a resin composition used for a semiconductor member.

[0079] A semiconductor package is constructed using an IC chip as an essential component and at least one member selected from molding resin, underfill material, mold underfill material, die bond material, prepreg for semiconductor package substrate, metal-clad laminate for semiconductor package substrate, and build-up material for printed circuit board for semiconductor package.

[0080] A semiconductor module is constructed using a semiconductor package as an essential component and at least one member selected from a prepreg for printed circuit boards, a metal-clad laminate for printed circuit boards, a build-up material for printed circuit boards, a solder resist material, a coverlay film, an electromagnetic shielding film, and an adhesive sheet for printed circuit boards.

[0081] <Paint composition> The hollow resin particles according to the embodiment of the present invention can impart an excellent appearance to a coating film containing the hollow resin particles, and therefore can be suitably used in a coating composition.

[0082] A coating composition according to an embodiment of the present invention includes hollow resin particles according to an embodiment of the present invention.

[0083] The coating composition according to the embodiment of the present invention preferably contains at least one selected from a binder resin and a UV curable resin. The binder resin may be only one type, or may be two or more types. The UV curable resin may be only one type, or may be two or more types.

[0084] As the binder resin, any suitable binder resin may be used as long as it does not impair the effects of the present invention. Examples of such binder resins include resins soluble in organic solvents or water, and emulsion-type aqueous resins that can be dispersed in water. Specific examples of binder resins include acrylic resins, alkyd resins, polyester resins, polyurethane resins, chlorinated polyolefin resins, and amorphous polyolefin resins.

[0085] As the UV-curable resin, any suitable UV-curable resin may be adopted as long as it does not impair the effects of the present invention. Examples of such UV-curable resins include polyfunctional (meth)acrylate resins and polyfunctional urethane acrylate resins, and polyfunctional (meth)acrylate resins are preferred, and polyfunctional (meth)acrylate resins having three or more (meth)acryloyl groups in one molecule are more preferred. Specific examples of polyfunctional (meth)acrylate resins having three or more (meth)acryloyl groups in one molecule include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol triacrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol triacrylate, and tripentaerythritol hexaacrylate.

[0086] When the coating composition according to the embodiment of the present invention contains at least one selected from a binder resin and a UV-curable resin, the content ratio may be any appropriate content ratio depending on the purpose. Typically, the hollow resin particles according to the embodiment of the present invention are preferably 5% by weight to 50% by weight, more preferably 10% by weight to 50% by weight, and even more preferably 20% by weight to 40% by weight, based on the total amount of the binder resin (in the case of an emulsion-type aqueous resin, solid content conversion) and at least one selected from a UV-curable resin and the hollow resin particles according to the embodiment of the present invention.

[0087] When a UV-curable resin is used, a photopolymerization initiator is preferably used in combination. As the photopolymerization initiator, any appropriate photopolymerization initiator can be used as long as it does not impair the effects of the present invention. Examples of such photopolymerization initiators include acetophenones, benzoins, benzophenones, phosphine oxides, ketals, α-hydroxyalkylphenones, α-aminoalkylphenones, anthraquinones, thioxanthones, azo compounds, peroxides (described in JP-A-2001-139663, etc.), 2,3-dialkyldione compounds, disulfide compounds, fluoroamine compounds, aromatic sulfonium compounds, onium salts, borate salts, active halogen compounds, and α-acyloxime esters.

[0088] The coating composition according to the embodiment of the present invention may contain a solvent. The solvent may be one type only, or may be two or more types. When the coating composition according to the embodiment of the present invention contains a solvent, the content ratio of the solvent may be any appropriate content ratio depending on the purpose.

[0089] As the solvent, any suitable solvent may be adopted as long as it does not impair the effects of the present invention. Such a solvent is preferably a solvent that can dissolve or disperse a binder resin or a UV-curable resin. For oil-based paints, such solvents include, for example, hydrocarbon solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; and ether solvents such as dioxane, ethylene glycol diethyl ether, and ethylene glycol monobutyl ether. For water-based paints, such solvents include, for example, water and alcohols.

[0090] The coating composition according to the embodiment of the present invention may be diluted to adjust the viscosity as necessary. As the diluent, any appropriate diluent may be adopted depending on the purpose. Examples of such diluents include the above-mentioned solvents. The diluent may be one type only or two or more types.

[0091] The coating composition according to the embodiment of the present invention may contain other components, such as a coating surface conditioner, a flowability conditioner, an ultraviolet absorber, a light stabilizer, a curing catalyst, an extender pigment, a color pigment, a metal pigment, a mica powder pigment, and a dye, as necessary.

[0092] When forming a coating film using the coating composition according to an embodiment of the present invention, any appropriate coating method may be adopted depending on the purpose. Examples of such coating methods include spray coating, roll coating, brush coating, coating reverse roll coating, gravure coating, die coating, comma coating, and spray coating.

[0093] When forming a coating film using the coating composition according to the embodiment of the present invention, any suitable forming method can be adopted as the forming method according to the purpose. For example, the forming method includes a method in which a coating film is formed by applying the coating composition to any coating surface of a substrate, drying the coating film, and then curing the coating film as necessary to form a coating film. For example, the substrate includes metal, wood, glass, plastic (PET (polyethylene terephthalate), PC (polycarbonate), acrylic resin, TAC (triacetyl cellulose), etc.).

[0094] <Thermal Insulation Resin Composition> The hollow resin particles according to the embodiment of the present invention can impart excellent heat insulation to a coating film containing the hollow resin particles, and therefore can be suitably used in a heat insulating resin composition. The coating film containing the hollow resin particles according to the embodiment of the present invention can exhibit excellent reflectance in the wavelength range from ultraviolet light to near infrared light.

[0095] The heat insulating resin composition according to an embodiment of the present invention includes hollow resin particles according to an embodiment of the present invention.

[0096] The heat insulating resin composition according to the embodiment of the present invention preferably contains at least one selected from a binder resin and a UV curable resin. For the binder resin and the UV curable resin, the above-mentioned explanation of the coating composition can be applied.

[0097] The heat insulating resin composition according to the embodiment of the present invention may contain a solvent. Regarding the solvent, the above description of the coating composition may be used.

[0098] The heat insulating resin composition according to the embodiment of the present invention may be diluted in order to adjust the viscosity as necessary. As the diluent, the above description of the coating composition may be used.

[0099] The heat insulating resin composition according to the embodiment of the present invention may contain other components, as necessary, for example, a coating surface conditioner, a flowability conditioner, an ultraviolet absorber, a light stabilizer, a curing catalyst, an extender pigment, a coloring pigment, a metal pigment, a mica powder pigment, and a dye.

[0100] When a coating film is formed using the heat insulating resin composition according to an embodiment of the present invention, the coating method and formation method may be the same as those described above for the coating composition.

[0101] <Light-diffusing resin composition> The hollow resin particles according to the embodiment of the present invention can impart excellent light diffusing properties to a coating film containing the hollow resin particles, and therefore can be suitably used in a light diffusing resin composition.

[0102] The light-diffusing resin composition according to an embodiment of the present invention contains hollow resin particles according to an embodiment of the present invention.

[0103] The light-diffusing resin composition according to the embodiment of the present invention preferably contains at least one selected from a binder resin and a UV-curable resin. The above-mentioned explanation of the coating composition can be applied to the binder resin and the UV-curable resin.

[0104] The light-diffusing resin composition according to the embodiment of the present invention may contain a solvent. Regarding the solvent, the above description of the coating composition may be used.

[0105] The light-diffusing resin composition according to the embodiment of the present invention may be diluted in order to adjust the viscosity as necessary. As the diluent, the above-mentioned description of the coating composition may be used.

[0106] The light-diffusing resin composition according to the embodiment of the present invention may contain other components, as necessary, such as a coating surface conditioner, a flowability conditioner, an ultraviolet absorber, a light stabilizer, a curing catalyst, an extender pigment, a coloring pigment, a metal pigment, a mica powder pigment, and a dye.

[0107] When a coating film is formed using the light-diffusing resin composition according to an embodiment of the present invention, the coating method and formation method may be the same as those described above for the coating composition.

[0108] <Light diffusion film> The hollow resin particles according to the embodiment of the present invention can impart excellent light diffusibility to a film having a coating film containing the hollow resin particles, and therefore can be suitably used in light diffusing films.

[0109] The light diffusing film according to an embodiment of the present invention includes hollow resin particles according to an embodiment of the present invention.

[0110] The light diffusion film according to the embodiment of the present invention includes a light diffusion layer formed from the light diffusing resin composition according to the embodiment of the present invention and a substrate. The light diffusion layer may be the outermost layer of the light diffusion film, or may not be the outermost layer. The light diffusion film according to the embodiment of the present invention may include any other appropriate layer depending on the purpose. Examples of such other layers include a protective layer, a hard coat layer, a planarizing layer, a high refractive index layer, an insulating layer, a conductive resin layer, a conductive metal fine particle layer, a conductive metal oxide fine particle layer, and a primer layer.

[0111] Examples of the substrate include metal, wood, glass, plastic film, plastic sheet, plastic lens, plastic panel, cathode ray tube, fluorescent display tube, and liquid crystal display panel. Examples of the plastics constituting the plastic film, plastic sheet, plastic lens, and plastic panel include PET (polyethylene terephthalate), PC (polycarbonate), acrylic resin, and TAC (triacetyl cellulose).

[0112] 2. Method for producing hollow resin particles A method for producing hollow resin particles according to an embodiment of the present invention comprises reacting 20 to 80 parts by weight of a compound (A) having an ether structure represented by formula (1) with 20 to 80 parts by weight of a monomer (B) that reacts with the compound (A) (the total amount of the compound (A) and the monomer (B) being 100 parts by weight), in an aqueous medium in the presence of a non-reactive solvent. [ka]

[0113] According to the above-described production method, the hollow resin particles according to the embodiment of the present invention can be easily produced.

[0114] The hollow resin particles according to the embodiment of the present invention can be obtained by reacting the compound (A) with the monomer (B) in an aqueous medium in the presence of a non-reactive solvent. Typically, the hollow resin particles according to the embodiment of the present invention can be produced by subjecting the compound (A) and the monomer (B) to a suspension polymerization reaction.

[0115] The suspension polymerization is typically a suspension polymerization using an aqueous phase containing an aqueous medium and an oil phase containing the compound (A), the monomer (B), and a non-reactive solvent, and preferably, the oil phase containing the compound (A), the monomer (B), and the non-reactive solvent is added to the aqueous phase containing an aqueous medium, dispersed, and heated to carry out the suspension polymerization.

[0116] As long as the oil phase can be present in the form of droplets in the aqueous phase, any suitable dispersion method can be adopted within the scope of the invention, which does not impair the effects of the present invention. Representative examples of such dispersion methods include a dispersion method using a homomixer or a homogenizer, such as a polytron homogenizer, an ultrasonic homogenizer, or a high-pressure homogenizer.

[0117] The polymerization temperature may be any suitable temperature suitable for suspension polymerization within a range that does not impair the effects of the present invention. Such a polymerization temperature is preferably 30°C to 80°C.

[0118] The polymerization time may be any appropriate time suitable for suspension polymerization, as long as it does not impair the effects of the present invention. Such a polymerization time is preferably 1 hour to 48 hours.

[0119] Post-heating, which is preferably carried out after polymerization, is a treatment suitable for obtaining hollow resin particles with a high degree of perfection.

[0120] The temperature of post-heating preferably carried out after polymerization may be any appropriate temperature within a range that does not impair the effects of the present invention. The temperature of such post-heating is preferably 70°C to 120°C.

[0121] The time for post-heating preferably carried out after polymerization can be any appropriate time within the range not impairing the effects of the present invention, and the time for such post-heating is preferably 1 hour to 24 hours.

[0122] For the compound (A) and the monomer (B), the explanation in the section <Polymer (P)> in <<1-2. Shell portion>> of <<1. Hollow resin particles>> can be directly applied.

[0123] The content ratio of the compound (A) and the monomer (B) can be directly cited from the explanation in the section <Polymer (P)> of <<1-2. Shell portion>> of <<1. Hollow resin particles>>.

[0124] Examples of the aqueous medium include water and a mixed medium of water and a lower alcohol (methanol, ethanol, etc.).

[0125] The amount of the aqueous medium used may be any appropriate amount within the range that does not impair the effects of the present invention. The amount of the aqueous medium used is typically an amount that allows the reaction to proceed appropriately in the suspension polymerization reaction carried out by adding an oil phase to an aqueous phase and suspending the oil phase, and is preferably 100 parts by weight to 5000 parts by weight, more preferably 150 parts by weight to 2000 parts by weight, relative to 100 parts by weight of the total amount of the compound (A), the monomer (B) and the non-reactive solvent.

[0126] The non-reactive solvent is a solvent that does not chemically react with either the compound (A) having an ether structure represented by formula (1) or the monomer (B) that reacts with the compound (A), and is preferably an organic solvent. The non-reactive solvent typically acts as a hollowing agent that gives the particles air space. Examples of the non-reactive solvent include heptane, hexane, toluene, cyclohexane, methyl acetate, ethyl acetate, methyl ethyl ketone, chloroform, and carbon tetrachloride. In terms of ease of removal from the hollow resin particles, the boiling point of the non-reactive solvent is preferably less than 100°C.

[0127] The non-reactive solvent as the hollowing agent may be a single solvent or a mixed solvent.

[0128] The amount of the non-reactive solvent added is preferably 20 parts by weight to 250 parts by weight based on 100 parts by weight of the total amount of the compound (A) and the monomer (B).

[0129] When reacting the compound (A) with the monomer (B), any suitable additive (C) that does not correspond to either the compound (A) or the monomer (B) may be used within a range that does not impair the effects of the present invention. The additive (C) may be one type or two or more types. The additive here does not include solvents such as aqueous media and non-reactive solvents.

[0130] The content of the additive (C) is preferably 0 to 40% by weight, more preferably 0 to 30% by weight, even more preferably 0 to 20% by weight, and particularly preferably 0 to 10% by weight, based on the total amount of the compound (A) and the monomer (B).

[0131] Any suitable additive may be used as the additive (C) as long as it does not impair the effects of the present invention. Examples of such additive (C) include a non-crosslinkable polymer, a dispersion stabilizer, a surfactant, and a polymerization initiator.

[0132] For the non-crosslinked polymer, the explanation in the section <Polymer (P)> in <<1-2. Shell portion>> of <<1. Hollow resin particles>> can be directly applied.

[0133] Examples of the dispersion stabilizer include polyvinyl alcohol, polycarboxylic acid, celluloses (hydroxyethyl cellulose, carboxymethyl cellulose, etc.), and polyvinylpyrrolidone. Inorganic water-soluble polymer compounds such as sodium tripolyphosphate can also be used. In addition, phosphates such as calcium phosphate, magnesium phosphate, aluminum phosphate, and zinc phosphate; pyrophosphates such as calcium pyrophosphate, magnesium pyrophosphate, aluminum pyrophosphate, and zinc pyrophosphate; poorly water-soluble inorganic compounds such as calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, and colloidal silica can also be used. Magnesium pyrophosphate is preferably used because it is relatively easy to remove from the hollow resin particles and is unlikely to remain on the surface of the hollow resin particles.

[0134] The amount of the dispersion stabilizer added is preferably 0.5 parts by weight to 10 parts by weight based on 100 parts by weight of the aqueous medium. The dispersion stabilizer may be of one kind or of two or more kinds.

[0135] Examples of the surfactant include anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.

[0136] Examples of anionic surfactants include non-reactive anionic surfactants such as alkyl sulfate, alkyl phosphate, alkylbenzene sulfonate, alkylnaphthalene sulfonate, alkane sulfonate, alkyldiphenyl ether sulfonate, dialkyl sulfosuccinate, monoalkyl sulfosuccinate, and polyoxyethylene alkylphenyl ether phosphate, and reactive anionic surfactants such as polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium salt, polyoxyethylene alkylpropenyl phenyl ether sulfate ammonium salt, and polyoxyalkylene alkenyl ether sulfate ammonium salt. The surfactant is not limited to a salt structure, and can also be, for example, an alkyl sulfate or an alkyl phosphate. Specific examples include lauryl sulfate and lauryl phosphate.

[0137] Examples of the cationic surfactant include alkyltrimethylammonium salts, alkyltriethylammonium salts, dialkyldimethylammonium salts, dialkyldiethylammonium salts, and N-polyoxyalkylene-N,N,N-trialkylammonium salts.

[0138] Examples of the zwitterionic surfactant include lauryl dimethylamine oxide, phosphate salts, and phosphite surfactants.

[0139] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polysorbitan fatty acid esters, polyoxyethylene alkylamines, glycerin fatty acid esters, and oxyethylene-oxypropylene block polymers.

[0140] The amount of the surfactant added is preferably 0.01% by weight to 5% by weight based on the total amount of the compound (A), the monomer (B) and the non-reactive solvent. The surfactant may be of one type or of two or more types.

[0141] As the polymerization initiator, any suitable polymerization initiator can be adopted within the scope that does not impair the effect of the present invention. Examples of such polymerization initiators include organic peroxides such as lauroyl peroxide, benzoyl peroxide, orthochlorobenzoyl peroxide, orthomethoxybenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-ethylhexanoate, and di-t-butyl peroxide; azo compounds such as 2,2'-azobisisobutyronitrile, 1,1'-azobiscyclohexanecarbonitrile, and 2,2'-azobis(2,4-dimethylvaleronitrile); and the like.

[0142] The content of the polymerization initiator is preferably within a range of 0.1% by weight to 5% by weight based on the total amount of the compound (A) and the monomer (B). The polymerization initiator may be of only one kind, or of two or more kinds. EXAMPLES

[0143] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".

[0144] <Measurement of Volume Average Particle Size (Examples 1 to 7, Example 10, Comparative Example 1)> The volume average particle size of the particles was measured by the Coulter method as follows. The volume average particle size of the particles was measured using a Coulter Multisizer (registered trademark) 3 (measuring device manufactured by Beckman Coulter, Inc.). The measurement was performed using an aperture calibrated according to the Multisizer (registered trademark) 3 user's manual issued by Beckman Coulter, Inc. The aperture used for the measurement was appropriately selected depending on the size of the particles to be measured, such as selecting an aperture having a size of 50 μm when the assumed volume average particle size of the particles to be measured is 1 μm or more and 10 μm or less, selecting an aperture having a size of 100 μm when the assumed volume average particle size of the particles to be measured is greater than 10 μm and less than 30 μm, selecting an aperture having a size of 280 μm when the assumed volume average particle size of the particles is greater than 30 μm and 90 μm or less, and selecting an aperture having a size of 400 μm when the assumed volume average particle size of the particles is greater than 90 μm and 150 μm or less. If the volume average particle diameter after measurement was different from the expected volume average particle diameter, the aperture was changed to one having an appropriate size and the measurement was performed again. Current (aperture current) and Gain (gain) were appropriately set according to the size of the selected aperture. For example, when an aperture having a size of 50 μm was selected, Current (aperture current) was set to -800 and Gain (gain) was set to 4, when an aperture having a size of 100 μm was selected, Current (aperture current) was set to -1600 and Gain (gain) was set to 2, and when apertures having sizes of 280 μm and 400 μm were selected, Current (aperture current) was set to -3200 and Gain (gain) was set to 1. The measurement sample was prepared by dispersing 0.1 g of particles in 10 ml of 0.1 wt % aqueous solution of nonionic surfactant using a touch mixer (manufactured by Yamato Scientific Co., Ltd., "TOUCHMIXER MT-31") and an ultrasonic cleaner (manufactured by Vervoclear Co., Ltd., "ULTRASONIC CLEANER VS-150") to prepare a dispersion. During the measurement, the beaker was gently stirred to prevent air bubbles from being introduced, and the measurement was terminated when 100,000 particles were measured. The volume average particle size of the particles was taken as the arithmetic mean of the particle size distribution based on the volume of 100,000 particles.

[0145] <Measurement of average particle size (Examples 8 and 9, Comparative Example 2)> Using the dynamic light scattering method, the Z-average particle size of the hollow resin particles or particles was measured, and the measured Z-average particle size was taken as the average particle size of the obtained hollow resin particles or particles. That is, first, the obtained slurry-like hollow resin particles or particles were diluted with ion-exchanged water and adjusted to a 0.1 wt% aqueous dispersion, irradiated with laser light, and the intensity of the scattered light scattered from the hollow resin particles or particles was measured as a function of time in microseconds. Then, the intensity distribution of the scattered light due to the detected hollow resin particles or particles was fitted to a normal distribution, and the Z-average particle size of the hollow resin particles or particles was determined by the cumulant analysis method for calculating the average particle size. The measurement of this Z-average particle size can be easily carried out with a commercially available particle size measuring device. In the following examples and comparative examples, the Z-average particle size was measured using a particle size measuring device (manufactured by Malvern, "Zetasizer Nano ZS"). Usually, commercially available particle size measuring devices are equipped with data analysis software, and the data analysis software can calculate the Z-average particle size by automatically analyzing the measurement data.

[0146] <Cross-section observation> The dried particles were mixed with a photocurable resin D-800 (manufactured by JEOL Ltd.), and a cured product was obtained by irradiating with ultraviolet light. Then, the cured product was cut with nippers, the cross-sectional part was smoothed using a cutter, and the sample was coated using a sputtering device "Auto Fine Coater JFC-1300" manufactured by JEOL Ltd. Next, the cross-section of the sample was photographed using the secondary electron detector of a scanning electron microscope "SU1510" manufactured by Hitachi High-Technologies Corporation.

[0147] <TEM measurement: Observation of the presence or absence and shape of the hollow of the hollow resin particles or particles> The hollow resin particles or particles as dry powder were subjected to surface treatment (10 Pa, 5 mA, 10 seconds) using an "Osmium Coater Neoc-Pro" coating device manufactured by Meiwa Force Systems Co., Ltd. The hollow resin particles or particles were then observed with a TEM (transmission electron microscope, "H-7600" manufactured by Hitachi High-Technologies Corporation) to confirm the presence or absence of hollowness and the shape of the hollow resin particles or particles. At this time, the accelerating voltage was set to 80 kV, and the magnification was set to 5,000 times or 10,000 times.

[0148] <Measurement of 5% thermal weight loss temperature when heating at 10℃ / min in a nitrogen atmosphere> The 5% thermal weight loss temperature was measured using a "TG / DTA6200, AST-2" differential thermal and thermogravimetric simultaneous measurement device manufactured by SII NanoTechnology Co., Ltd. The sampling method and temperature conditions were as follows. The sample for measurement was prepared by filling the bottom of a platinum measuring container with 10.5±0.5 mg of sample without leaving any gaps. The 5% thermal weight loss temperature was measured using alumina as the reference material under a nitrogen gas flow rate of 230 mL / min. The TG / DTA curve was obtained by heating the sample from 30°C to 500°C at a heating rate of 10°C / min. The temperature at which the weight loss was 5% was calculated from the obtained curve using the analysis software attached to the device, and was determined as the 5% thermal weight loss temperature.

[0149] Example 1 An oil phase was prepared by mixing 2.5 g of a bifunctional polyphenylene ether oligomer (trade name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a compound having an ether structure represented by formula (1), 2.5 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), 5.0 g of heptane, 0.05 g of 2,2'-azobis(2,4-dimethylvaleronitrile) (trade name "V-65", manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 0.004 g of lauryl phosphoric acid. The oil phase was added to 32 g of a 2 wt % aqueous dispersion of magnesium pyrophosphate as the aqueous phase, and a suspension was prepared using a Polytron homogenizer "PT10-35" (manufactured by Central Scientific Trading Co., Ltd.). The resulting suspension was heated at 50°C for 24 hours to carry out a reaction. Hydrochloric acid was added to the resulting slurry to decompose the magnesium pyrophosphate, and the solids were then separated by dehydration through filtration, purified by repeated washing with water, and dried at 60°C to obtain particles (1). A cross-sectional photograph of the obtained particle (1) is shown in Figure 2. It was confirmed that the obtained particle (1) was a mixture of hollow resin particles having one hollow region surrounded by a shell, and hollow resin particles having a porous structure surrounded by a shell. The average particle size of the obtained particles (1) was 16.3 μm. The 5% thermal weight loss temperature of the obtained particles (1) was 306°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0150] Example 2 Particles (2) were obtained in the same manner as in Example 1, except that the amount of bifunctional polyphenylene ether oligomer (product name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Inc.) as the compound having an ether structure represented by formula (1) was 3.0 g, and the amount of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) was 2.0 g. A cross-sectional photograph of the obtained particle (2) is shown in Fig. 3. It was confirmed that the obtained particle (2) was a hollow resin particle consisting of one hollow region surrounded by a shell. The average particle size of the obtained particles (2) was 15.2 μm. The 5% thermal weight loss temperature of the obtained particles (2) was 320°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0151] Example 3 Particles (3) were obtained in the same manner as in Example 1, except that the amount of bifunctional polyphenylene ether oligomer (product name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Inc.) as the compound having an ether structure represented by formula (1) was 3.5 g, and the amount of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) was 1.5 g. A cross-sectional photograph of the obtained particle (3) is shown in Fig. 4. It was confirmed that the obtained particle (3) was a hollow resin particle consisting of one hollow region surrounded by a shell. The average particle size of the obtained particles (3) was 13.9 μm. The 5% thermal weight loss temperature of the obtained particles (3) was 309°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0152] Example 4 Particles (4) were obtained in the same manner as in Example 1, except that 2.5 g of a reactive low-molecular-weight polyphenylene ether (trade name "Noryl (registered trademark) SA9000-111 resin", manufactured by SABIC Corporation) was used as a compound having an ether structure represented by formula (1) instead of 2.5 g of a bifunctional polyphenylene ether oligomer (trade name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Inc.) as a compound having an ether structure represented by formula (1). A cross-sectional photograph of the obtained particle (4) is shown in Fig. 5. It was confirmed that the obtained particle (4) was a hollow resin particle having a porous structure with the hollow space surrounded by a shell. The average particle size of the obtained particles (4) was 16.5 μm. The 5% thermal weight loss temperature of the obtained particles (4) was 373°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0153] Example 5 Particles (5) were obtained in the same manner as in Example 2, except that 3.0 g of a reactive low-molecular-weight polyphenylene ether (product name "Noryl (registered trademark) SA9000-111 resin", manufactured by SABIC Corporation) was used as a compound having an ether structure represented by formula (1) instead of 3.0 g of a bifunctional polyphenylene ether oligomer (product name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Inc.) as a compound having an ether structure represented by formula (1). A cross-sectional photograph of the obtained particle (5) is shown in Fig. 6. It was confirmed that the obtained particle (5) was a hollow resin particle having a porous structure with the hollow space surrounded by a shell. The average particle size of the obtained particles (5) was 15.6 μm. The 5% thermal weight loss temperature of the obtained particles (5) was 420°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0154] Example 6 Particles (6) were obtained in the same manner as in Example 1, except that 2.5 g of a bifunctional polyphenylene ether oligomer (trade name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a compound having an ether structure represented by formula (1), 2.5 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), and 5.0 g of heptane were replaced with 1.8 g of a reactive low molecular weight polyphenylene ether (trade name "Noryl (registered trademark) SA9000-111 resin", manufactured by SABIC Corporation) as a compound having an ether structure represented by formula (1), 1.2 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), 5.0 g of heptane, and 2.0 g of toluene. A cross-sectional photograph of the obtained particle (6) is shown in Fig. 7. It was confirmed that the obtained particle (6) was a hollow resin particle having a porous structure with the hollow space surrounded by a shell. The average particle size of the obtained particles (6) was 15.1 μm. The 5% thermal weight loss temperature of the obtained particles (6) was 415°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0155] Example 7 Particles (7) were obtained in the same manner as in Example 1, except that 2.5 g of a bifunctional polyphenylene ether oligomer (trade name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a compound having an ether structure represented by formula (1), 2.5 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), and 4.0 g of reactive low molecular weight polyphenylene ether (trade name "Noryl (registered trademark) SA9000-111 resin", manufactured by SABIC Corporation) as a compound having an ether structure represented by formula (1), 1.0 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), 4.0 g of heptane, and 1.0 g of cyclohexane were used instead of 5.0 g of heptane. A cross-sectional photograph of the obtained particle (7) is shown in Fig. 8. It was confirmed that the obtained particle (7) was a hollow resin particle having a porous structure with the hollow surrounded by a shell. The average particle size of the obtained particles (7) was 13.1 μm. The 5% thermal weight loss temperature of the obtained particles (7) was 428°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0156] Example 8 An oil phase was prepared by mixing 1.5 g of a bifunctional polyphenylene ether oligomer (product name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Inc.) as a compound having an ether structure represented by formula (1), 1.5 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), 3.0 g of heptane, and 0.09 g of Perloyl L (manufactured by NOF Corporation) as a polymerization initiator. Next, 34 g of ion-exchanged water and 0.0128 g of Rapisol A-80 (NOF Corporation) were mixed to prepare an aqueous phase. The oil phase was added to the aqueous phase, and a suspension was prepared using an ultrasonic homogenizer (manufactured by Branson, "SONIFIER450", conditions: Duty Cycle = 50%, Output Control = 5, processing time 3 minutes). The resulting suspension was heated at 70°C for 4 hours to carry out a reaction. The resulting slurry was heated at 100°C for 24 hours to obtain dried particles (8). A TEM photograph of the obtained particle (8) is shown in Fig. 9. It was confirmed that the obtained particle (8) was a hollow resin particle having a porous structure with the hollow space surrounded by a shell. The average particle size of the obtained particles (8) was 320 nm. The 5% thermal weight loss temperature of the obtained particles (8) was 315°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0157] Example 9 An oil phase was prepared by mixing 1.08 g of a reactive low-molecular-weight polyphenylene ether (product name "Noryl (registered trademark) SA9000-111 resin", manufactured by SABIC Corporation) as a compound having an ether structure represented by formula (1), 0.72 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)), 3.0 g of heptane, 1.2 g of toluene, and 0.03 g of Perloyl L (manufactured by NOF Corporation) as a polymerization initiator. Next, 34 g of ion-exchanged water and 0.0085 g of Rapisol A-80 (NOF Corporation) were mixed to prepare an aqueous phase. The oil phase was added to the aqueous phase, and a suspension was prepared using an ultrasonic homogenizer (manufactured by Branson, "SONIFIER450", conditions: Duty Cycle = 50%, Output Control = 5, processing time 3 minutes). The resulting suspension was heated at 70°C for 4 hours to carry out a reaction. The resulting slurry was heated at 100°C for 24 hours to obtain dried particles (9). A TEM photograph of the obtained particle (9) is shown in Fig. 10. It was confirmed that the obtained particle (9) was a hollow resin particle having a porous structure with the hollow space surrounded by a shell. The average particle size of the obtained particles (9) was 379 nm. The 5% thermal weight loss temperature of the obtained particles (9) was 399°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0158] Example 10 Particles (10) were obtained in the same manner as in Example 1, except that the amount of bifunctional polyphenylene ether oligomer (product name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Inc.) as the compound having an ether structure represented by formula (1) was 2.0 g, and the amount of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) was 3.0 g. A cross-sectional photograph of the obtained particle (10) is shown in Fig. 11. It was confirmed that the obtained particle (10) was a hollow resin particle having a porous structure with the hollow surrounded by a shell. The average particle size of the obtained particles (10) was 14.4 μm. The 5% thermal weight loss temperature of the obtained particles (10) was 312°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0159] Example 11 Particles (11) were obtained in the same manner as in Example 1, except that 2.0 g of reactive low-molecular-weight polyphenylene ether (trade name "Noryl (registered trademark) SA9000-111 resin", manufactured by SABIC Corporation) and 3.0 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) were used as compounds having an ether structure represented by formula (1) instead of 2.5 g of bifunctional polyphenylene ether oligomer (trade name "OPE-2St 1200", manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 2.5 g of divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) as compounds having an ether structure represented by formula (1). A cross-sectional photograph of the obtained particle (11) is shown in Fig. 12. It was confirmed that the obtained particle (11) was a hollow resin particle having a porous structure with the hollow surrounded by a shell. The average particle size of the obtained particles (11) was 12.7 μm. The 5% thermal weight loss temperature of the obtained particles (11) was 366°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0160] Comparative Example 1 An oil phase was prepared by mixing 2.5 g of methyl methacrylate, 2.5 g of ethylene glycol dimethacrylate, 5 g of cyclohexane, 0.05 g of 2,2'-azobis(2,4-dimethylvaleronitrile) (product name "V-65", Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 0.004 g of lauryl phosphoric acid. The oil phase was added to 32 g of a 2 wt % aqueous dispersion of magnesium pyrophosphate as the aqueous phase, and a suspension was prepared using a Polytron homogenizer PT10-35 (manufactured by Central Scientific Trading Co., Ltd.). The resulting suspension was heated at 50°C for 24 hours to carry out a reaction. Hydrochloric acid was added to the resulting slurry to decompose the magnesium pyrophosphate, and the solid content was separated by dehydration through filtration, purified by repeated washing with water, and then dried at 60°C to obtain particles (C1) as a dry powder. A cross-sectional photograph of the obtained particle (C1) is shown in Fig. 13. It was confirmed that the obtained particle (C1) was a hollow resin particle having one hollow region surrounded by a shell. The average particle size of the obtained particles (C1) was 8.3 μm. The 5% thermal weight loss temperature of the obtained particles (C1) was 245°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0161] Comparative Example 2 An oil phase was prepared by mixing 1.74 g of methyl methacrylate (MMA), 1.74 g of dipentaerythritol hexaacrylate (ADPH) (Shin-Nakamura Chemical Co., Ltd.), 2.4 g of toluene, 0.126 g of polystyrene (non-crosslinked, weight average molecular weight 300,000), and 0.104 g of Perloyl L (polymerization initiator, NOF Corporation). Next, 34 g of ion-exchanged water and 0.034 g of Rapisol A-80 (surfactant, NOF Corporation) were mixed to prepare an aqueous phase. The oil phase was added to the aqueous phase, and a suspension was prepared using an ultrasonic homogenizer (BRANSON, "SONIFIER450", conditions: Duty Cycle = 50%, Output Control = 5, processing time 3 minutes). The suspension was polymerized by heating at 70°C for 4 hours to obtain a slurry. The slurry was heated at 100°C for 24 hours to obtain particles (C2) as a dry powder. A TEM photograph of the obtained particle (C2) is shown in Figure 14. It was confirmed that the obtained particle (C2) was a hollow resin particle consisting of one hollow region surrounded by a shell. The average particle size of the obtained particles (C2) was 478 nm and the particle density was 0.614 g / cm 3 It was. The 5% thermal weight loss temperature of the obtained particles (C2) was 327°C when the temperature was increased at 10°C / min in a nitrogen atmosphere. The blending amounts are shown in Table 1.

[0162] [Table 1]

[0163] <Performance evaluation 1: Dielectric constant and dielectric tangent evaluation 1> 0.4 g of the particles obtained in each of the Examples and Comparative Examples and 10 g of ultra-high heat-resistant polyimide varnish (product name "SPIXAREA HR (registered trademark) 002", manufactured by Somar Co., Ltd.) were degassed and stirred using a planetary mixing degasser (manufactured by KURABO Corporation, "Mazerustar KK-250") to prepare a mixture for evaluation. The mixture for evaluation was applied to a 5 mm thick glass plate using an applicator set to a wet thickness of 250 μm, and then heated at 120°C for 10 minutes, 180°C for 180 minutes, and 270°C for 60 minutes to remove the solvent, and then cooled to room temperature to obtain a film sample containing each particle. The dielectric constant and dielectric loss tangent of the obtained film were evaluated using the cavity resonance method (measurement frequency: 5.8 GHz). The results are shown in Table 2.

[0164] [Table 2]

[0165] From the results in Table 2, it can be confirmed that the hollow resin particles provided by the present invention have the effect of lowering the relative dielectric constant and dielectric dissipation factor of the substrate, and are therefore effective for the purpose of achieving low dielectric constant and low dielectric dissipation factor of semiconductor materials.

[0166] <Performance evaluation 2: Dielectric constant and dielectric tangent evaluation 2> 0.425 g of the particles obtained in the Examples and Comparative Examples, 12.1 g of ethyl acetate, and 1.7 g of solvent-soluble polyimide KPI-MX300F (manufactured by Kawamura Sangyo Co., Ltd.) were mixed and degassed using a planetary mixing degasser (manufactured by KURABO Corporation, "Mazerustar KK-250") to prepare a mixture for evaluation. The mixture for evaluation was applied to a 5 mm thick glass plate using an applicator set to a wet thickness of 250 μm, and then heated at 60°C for 30 minutes, 90°C for 10 minutes, 150°C for 30 minutes, and 200°C for 30 minutes to remove ethyl acetate. Film samples containing each particle were then obtained by cooling to room temperature. The dielectric constant and dielectric loss tangent of the obtained films were evaluated using the cavity resonance method (measurement frequency: 5.8 GHz). The results are shown in Table 3.

[0167] [Table 3]

[0168] From the results in Table 3, it can be confirmed that the hollow resin particles provided by the present invention have the effect of lowering the relative dielectric constant and dielectric dissipation factor of the substrate, and are therefore effective for the purpose of achieving low dielectric constant and low dielectric dissipation factor of semiconductor materials.

[0169] <Performance evaluation 3: Moisture content evaluation> The particles obtained in each of the Examples and Comparative Examples were subjected to a moisture absorption treatment under the following conditions. The particles obtained in each Example and Comparative Example were placed in a thermohygrostat at a temperature of 40±1°C and a relative humidity of 95%, and after 96 hours were removed and cooled for 30 minutes in an environment (temperature 20±1°C, humidity 65±5%). After cooling, the moisture content was measured. The moisture content was measured by setting 0.1 g of the particles obtained in each Example and Comparative Example as a sample in a Karl Fischer moisture analyzer "CA-200" manufactured by Mitsubishi Chemical Analytech Co., Ltd. and a moisture vaporizer "VA-236S". The anolyte and catholyte used in the measurement were "Aquamicron (registered trademark) AX" and "Aquamicron (registered trademark) CXU" manufactured by Mitsubishi Chemical Co., Ltd., respectively. The measurement (vaporization) temperature was 250°C. Nitrogen was used as the carrier gas. The flow rate of the carrier gas was 150 mL / min. The number of tests for the sample was three. The moisture content of only the air at the sample collection site was measured twice, and the average value was used as the blank value. The blank value was subtracted from each measurement result and divided by the sample weight to obtain the moisture content (wt%) of the sample. The moisture content (wt%) of the sample was calculated using the following formula. Moisture content (wt%) = [measured moisture content (μg) - blank moisture content (μg)] ÷ 1,000,000 ÷ sample weight (g) × 100 The final result was the average of the three measurements, which was taken as the moisture content (wt%) of the sample. The results are shown in Table 4.

[0170] [Table 4]

[0171] The results in Table 4 show that the hollow resin particles provided by the present invention have a lower moisture content after moisture absorption treatment compared to conventional hollow resin particles, and are suitable for the purpose of achieving lower dielectric constant and lower dielectric tangent of semiconductor materials.

[0172] <Performance evaluation 4: Thermal insulation evaluation> 2.5 g of the particles (1) obtained in Example 1 was added to 10 g of a commercially available water-based paint (manufactured by Asahipen Co., Ltd., product name "Water-based Multi-Purpose Color Clear"), and the mixture was degassed and stirred using a planetary mixing degasser (manufactured by KURABO Corporation, "Mazerustar KK-250") to prepare a paint for evaluation. The paint for evaluation was applied to the black side of the hiding power test paper with an applicator set to a wet thickness of 250 μm, and then thoroughly dried at room temperature to obtain a sample plate for evaluating light reflectivity. The reflectivity of the sample plate for evaluating light reflectivity to ultraviolet light, visible light, and near infrared light was evaluated in the following order of points. A UV-Vis-NIR spectrophotometer (Shimadzu Corporation, Solid Spec3700) was used to measure the reflectance, and the reflectance characteristics of the coated surface of the sample plate for evaluating light reflectance, from UV to NIR (wavelength 300 nm to 2500 nm), were measured as reflectance (%). The measurements were performed using a 60 mm Φ integrating sphere and Spectralon as a standard white plate. The obtained results are shown in Figure 15. As shown in Figure 15, it was found that the film had a high reflectance of 40% or more for almost all wavelengths from ultraviolet light to near infrared light.

[0173] <Performance evaluation 5: Coating appearance evaluation> 2 parts by weight of the particles (1) obtained in Example 1 and 20 parts by weight of a commercially available acrylic water-based glossy paint (manufactured by Campe Papio Co., Ltd., product name "Super Hit") were mixed for 3 minutes using a stirring and defoaming device, and then defoamed for 1 minute to obtain a coating composition. The resulting coating composition was applied onto an ABS resin (acrylonitrile-butadiene-styrene resin) plate using a coating device equipped with a blade with a clearance of 75 μm, and then dried to obtain a coating film. The resulting coating composition was spray-coated onto a 3 mm-thick acrylic plate to prepare a 50 μm-thick matte coating film. The resulting coating film had no visible bumps and had good matte properties.

[0174] <Performance evaluation 6: Light diffusion evaluation> 7.5 parts by weight of the particles (1) obtained in Example 1, 30 parts by weight of an acrylic resin (manufactured by DIC Corporation, product name "ACRYDIC A811"), 10 parts by weight of a crosslinking agent (manufactured by DIC Corporation, product name "VM-D"), and 50 parts by weight of butyl acetate as a solvent were mixed for 3 minutes using a stirring and defoaming device and degassed for 1 minute to obtain a light-diffusing resin composition. The obtained light-diffusing resin composition was applied onto a 125 μm-thick PET film using a coating device equipped with a blade with a clearance of 50 μm, and then dried at 70° C. for 10 minutes to obtain a light-diffusing film. The total light transmittance and haze of the obtained light diffusion film were measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH 2000") according to JIS K 7361-1: 1997 and JIS K 7136: 2000, respectively. The higher the diffusivity of light transmitted through the light diffusion film (transmitted light), the higher the haze value. As a result of the measurements, the haze was 40.2% and the total light transmittance was 81.5%, and it was confirmed that the obtained light diffusion film had excellent light diffusion properties. [Industrial Applicability]

[0175] The hollow resin particles according to the embodiment of the present invention and the hollow resin particles obtained by the manufacturing method according to the embodiment of the present invention can be used as semiconductor materials, etc. The hollow resin particles according to the embodiment of the present invention and the hollow resin particles obtained by the manufacturing method according to the embodiment of the present invention can be applied to applications such as resin compositions for semiconductor members, coating compositions, heat insulating compositions, light diffusing compositions, and light diffusing films.

Claims

1. A hollow resin particle having a shell portion and a hollow portion surrounded by the shell portion, The average particle size is 0.1 μm to 50.0 μm, The shell portion contains a polymer (P) having an ether structure represented by formula (1), The polymer (P) is obtained by reacting a compound (A) having an ether structure represented by formula (1) with a monomer (B) which reacts with the compound (A), the compound (A) is a bifunctional polyphenylene ether oligomer having a number average molecular weight of 500 to 3500 or a reactive low molecular weight polyphenylene ether having a number average molecular weight of 500 to 3500, The monomer (B) contains an aromatic crosslinkable monomer and an aromatic monofunctional monomer. Hollow resin particles. 【Chemistry 1】

2. 2. The hollow resin particles according to claim 1, wherein the hollow resin particles have a 5% thermal weight loss temperature of 300° C. or higher when heated at a rate of 10° C. / min in a nitrogen atmosphere.

3. The hollow resin particle according to claim 1 or 2, which is used in a resin composition for a semiconductor member.

4. 3. The hollow resin particle according to claim 1 or 2, which is used in a coating composition.

5. The hollow resin particle according to claim 1 or 2, which is used in a heat insulating resin composition.

6. The hollow resin particle according to claim 1 or 2, which is used in a light-diffusing resin composition.

7. The hollow resin particle according to claim 1 or 2, which is used for a light diffusing film.

8. A resin composition for a semiconductor member, comprising the hollow resin particles according to claim 1 or 2.

9. A coating composition comprising the hollow resin particles according to claim 1 or 2.

10. A heat insulating resin composition comprising the hollow resin particles according to claim 1 or 2.

11. A light-diffusing resin composition comprising the hollow resin particles according to claim 1 or 2.

12. A light-diffusing film comprising the hollow resin particles according to claim 1 or 2.

13. A method for producing hollow resin particles according to any one of claims 1 to 7, comprising the steps of: reacting 20 to 80 parts by weight of a compound (A) having an ether structure represented by formula (1) with 80 to 20 parts by weight of a monomer (B) that reacts with the compound (A) (the total amount of the compound (A) and the monomer (B) being taken as 100 parts by weight) in an aqueous medium in the presence of a non-reactive solvent; the compound (A) is a bifunctional polyphenylene ether oligomer having a number average molecular weight of 500 to 3500 or a reactive low molecular weight polyphenylene ether having a number average molecular weight of 500 to 3500, The monomer (B) contains an aromatic crosslinkable monomer and an aromatic monofunctional monomer. A method for producing hollow resin particles. 【Chemistry 2】

Citation Information

Patent Citations

  • Foamable thermoplastic resin beads

    JP1989065140A

  • Heat-resistant foam resin particles and its production

    JP1998279725A

  • Crosslinked resin particle, composition for organic insulation material, organic insulation material, sealant and circuit board

    JP2000313818A

  • Hollow polymer fine particle and method for producing the same

    JP2002080503A

  • Coating material and coating film formation method

    JP2015134912A